Three new species of Ecuadorian Rhinotragini (Coleoptera, Cerambycidae) - Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2017)
Three new species of Rhinotragini are described from Ecuador: Paraeclipta ecuadorensis, Odontocera magnifica and Lygrocharis setosus.